P-E11 CD8+D28-T cells: A major T cell subset with diverse functions in chronic HBV infection. (March 2017) - Nandi, Madhuparna; Pal, Sourina; Ghosh, Sumantra; Kottilil, Shyamasundaran; Banerjee, Soma; Santra, Amal; Chowdhury, Abhijit; Datta, Simanti
Abstract : CD8 + T cells, considered as key players in viral clearance, are functionally attenuated in chronic HBV infection (CHI). A prominent feature of CD8+ T cells in CHI is the downregulation of CD28 molecule that is essential for T cell activation. Different studies had assigned diverse functional attributes to these CD8+ D28-T cells in various disease contexts. The present study focused on phenotypic and functional characterization of CD8+ D28-T cells in CHI to gain an insight into their contribution in disease pathogenesis. We observed significant accumulation of CD8+ D28-T cells in both HBeAg positive (e+) and HBeAg negative (e-) CHB patients as compared to inactive carriers (IC) and healthy subjects. Flow cytometry analysis of CD8+ D28− T cells revealed significantly (about 1.5 fold) high expression of FoxP3, IL-10, TGF-β and low CD127 expression than their CD8+ D28+ + T cell counterparts, in e(+) and e(-) CHB patients, suggesting their enhanced immunosuppressive activity. Concurrently, a profound (almost 4–6 times) increase in expression of perforin, granzyme, NKG2D, CD57, IFN-γ and TNF-α in CD8+ D28− T cells from CHB was seen, as compared to CD8+ D28+ + T cells denoting their high cytolytic predisposition. Our data depicted a comprehensively greater fold change in expression of cytotoxic proteins than that of suppressive markers by CD28-T cells as compared to CD28+ + T cells, suggesting a predominant cytolytic nature of CD28− T cells. CXCR3 expression on both CD28 counterparts was comparable implying analogous predilection of both to be recruited to liver. Thus CD8+ D28-T lymphocytes represent a major and a primarily cytotoxic T cell subset which might potentially contribute to disease severity in active hepatitis.